Subjective well-being in elderly: focusing from Grandparents Circle (Original) (Revista científica Olimpia, 2019)
This study was carried up in the “Grandparents Circle Vilma Espín” in Bayamo City. The sample was formed by 31 elderly (29 women y 2 men), with chronological aged average of 67, 4 years old. The general objective is to design a psychosocial actions system from Grandparents Circle, for to raise the subjective well-being in these older persons. With investigation methods of theoretic and empiric knowledge, the author obtained a psychosocial characterization, the creation and application of the actions system. The result was satisfactory in the raise of the subjective well-being. These results constitute a practical contribution to process of the communitarian physical activity for elderly.
Keywords: subjective well-being; elderly; grandparents circle; physical activity; actions system